The influence of oxime and anticholinergic drug selection on the potency of antidotal treatment to counteract acute toxic effects of tabun in mice - Kassa, Jirí (Neurotoxicity research, 2006)
The influence of newly developed oximes, K027 [1-(4-hydroxyiminomethylpyridinium)-3-(4-carbamoylpyridinium) propane dibromide] and K048 [1-(4-hydroxyiminomethylpyridinium)-3-(4-carbamoylpyridinium) butane dibromide], or currently used oximes (pralidoxime, obidoxime, trimedoxime, HI-6) and anticholinergic drugs (atropine, benactyzine) on the ability of antidotal treatment to eliminate tabun-induced acute toxic effects was studied in mice. The therapeutical efficacy of trimedoxime and both newly developed oximes (K027, K048) is significantly higher than the potency of pralidoxime (regardless of the choice of anticholinergic drug), obidoxime (in the case of its combination with atropine) and the oxime HI-6 (in the case of its combination with benactyzine). All studied oximes with the exception of pralidoxime and the oxime HI-6, when combined with benactyzine, appear to be more efficacious in the elimination of toxic effects of the lethal dose of tabun than their combination with atropine. The findings support the hypothesis that the choice of acetylcholinesterase reactivators as well as the anticholinergic drug selection are important for the effectiveness of an antidotal mixture in the case of antidotal treatment of tabun-induced acute poisonings.
Keywords: hodnocení léčiv; Animals; Chemical Warfare Agents; antidota; Lethal Dose 50; lékové interakce; Drug Interactions; oximy; otrava organofosfáty; LD50; Mice; chemické bojové látky; Antidotes; myši; Organophosphates; Oximes; Drug Evaluation; Male; organofosfáty; reaktivátory cholinesterasy; Cholinergic Antagonists; zvířata; mužské pohlaví; Organophosphate Poisoning; cholinergní antagonisté; Cholinesterase Reactivators